Knowledge and acceptability of cervical cancer screening among adult women in gynecological OPD in Bharatpur Hospital. - Shrestha,Bishnu Kumari (2017)
ABSTRACT: Pap smear is the very significant screening test for reduction of incidence and mortality from cervical cancer. The objective of this study was to find out the Knowledge and acceptability of cervical cancer screening among adult women in Gynecological OPD of Bharatpur Hospital. The study population consisted of 425 of Gynaepatients who had 30-59 year of age. A descriptive research design was used. Data was collected by using semi structure interview schedule. Non-probability purposive sampling technique was used to select 425 patients. Descriptive statistics such as frequency, percentage, mean and standard deviation and inferential statistics chi-square, likelihood ratio test was used to find out the association between knowledge and acceptability of cervical cancer and different factors. Majority 211 (49.6%) of the participant age group were 30-39 years. The Mean age of participants was 40.07 (SD=7.9). Majority 247 (58.1%) respondents had good knowledge in cervical cancer screening and majority 282 (66.4%) respondent accepted pap smear test. Mean knowledge score on sign and symptom of cervical cancerwas 3.7 (62.1%), risk factor 7.3 (72.8%),preventive measure 4.1 (82%) and total mean knowledge on cervical cancer was 16 (67%). Mean knowledge of pap smear test was 17.7 (65.2%.), overall mean knowledge of cervical cancer screening score was 27 (66.2 %). There was association between respondents knowledge of cervical cancer screening and educational status (p=0.04), religion (p=0.01) at 0.05 level of significance. There was association between respondents' level of Knowledge and acceptability of cervical cancer screening (p=0.02) at 0.05 level of significance Based on study findings it is concluded that majority of participant had never been screening for cervical cancer, information get from health care provider was poor and acceptability rate is low. So the study recommends others that health care provider should engage more on giving information Education, communication (IEC) at all level of delivery towards cervical cancer screening.